Impact of Power Tariff Policy on Development of Grid - Connected Rooftop PV Systems in Vietnam - Nguyen, Thuy Linh; Le, Thi Minh Chau; Nguyen, Duy Khiem; Tran, Dinh Long (Old Journal, 2018)
In grid-connected rooftop photovoltaic power systems, the generated electricity from these power systems can be sold to the electricity serving ultity. This arrangement provide payback for investors to be able to take the investment of their PV power system installation back and the payback period of the rooftop PV power system installation depends on the tariff policy as well. In this paper, the impact of main factors of the tariff policy are considered such as: (1) the Feed-in-tariff policy for renewable resources in general and for the solar energy in particular, (2) Block meter tariff and (3) time-of-use tariff.